Chitosan-manganese oxide composite photocatalyst for activating PMS as well as preparation process and application of chitosan-manganese oxide composite photocatalyst
The activation of PMS by chitosan-manganese oxide composite photocatalyst solves the problem of poor dye degradation effect of existing oxidants, achieving efficient degradation of methylene blue and toluidine blue, and having good recycling performance.
Patent Information
- Application Number
- CN202411789759.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-06
AI Technical Summary
Existing oxidants are not effective in degrading dyes and cannot meet application needs.
The chitosan-manganese oxide composite photocatalyst is used to improve the degradation efficiency of the dye by combining chitosan with manganese oxide and activating peroxy monosulfate (PMS) under light.
The degradation rates of methylene blue (MB) and toluidine blue (TB) were significantly improved, reaching 94.5% and 92.2%, respectively, and the catalyst has good recycling stability.
Smart Images

Figure CN119608247A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalyst preparation, and in particular relates to a chitosan-manganese oxide composite photocatalyst for activating PMS, a preparation process and an application thereof. Technical Background
[0002] In recent years, researchers have found that it is increasingly difficult to remove organic dyes from industrial wastewater, and have therefore adopted a variety of physical, chemical and biological methods, such as adsorption, membrane filtration, advanced oxidation processes (AOPs, such as photocatalytic oxidation, Fenton, Fenton-like, etc.), ion exchange, and catalytic reduction. Among these methods, advanced oxidation processes have the advantages of higher redox potential, low cost, high efficiency, environmentally friendly photooxidation process, sustainable solar energy collection, and high reaction selectivity compared to other methods.
[0003] Advanced oxidation processes (AOPs) can produce reactive oxygen species (ROS) with high redox potential to degrade pollutants in wastewater. Photocatalytic oxidation can utilize the abundant sunlight on Earth to degrade pollutants without producing other harmful gases and is widely used. Photocatalysis is to provide an activated area on the surface of semiconductor materials with the assistance of ultraviolet or visible light radiation, and then a redox reaction occurs on the semiconductor material. The products of the redox cycle will produce OH· and SO4 -· group, in which the generation of reactive oxygen species (ROS) can effectively oxidize and degrade the target pollutants. Therefore, a series of studies have been conducted on how to improve the degradation rate of target pollutants. Faced with many elements for preparing photocatalysts, transition metals are usually selected for the following reasons: First, the light absorption range of transition metals is relatively wide, which can effectively utilize light energy; second, there are multiple valences, which can produce defects on the surface or change its crystallinity, prolonging the recombination time of electrons and holes; third, when doped with transition metal elements, it can improve its adsorption performance for reactants; fourth, AOPs can use transition metals to activate peroxymonosulfate to degrade dyes. Among the many transition metal elements, researchers have studied the degradation of dyes under certain conditions by transition metal oxides represented by cobalt, magnesium, bismuth, and cobalt-manganese bimetallics. Among them, manganese is abundant in the earth's crust, second only to iron, and has a variety of oxidation forms. It has the advantages of low cost, good stability, environmental friendliness, and high catalytic activity, making it the main research material today. Among transition metal oxides, manganese oxides include MnO, MnO2, Mn2O3, etc., because their structure and composition are relatively special among oxides. Among them, the high stability and physicochemical properties of MnO2 in the environment have attracted widespread attention from researchers. Studies by Moon SA et al. have shown that MnO2 has a higher ability to degrade Congo red than Ag and CuO nanoparticles. Liu et al. used a hydrothermal method to prepare rod-shaped MnO2, which degraded methyl violet by up to 89.5%. Rabani I et al. studied the degradation rate of MB and CV by α-MnO2-Fe3O4 flower-like structure under visible light irradiation, which was as high as 93% or more. Dong et al.'s study showed that MnO2 activated PS under light, thereby effectively degrading bisphenol A. Sdy et al. found that when MnO2 of different crystal phases activated PMS to degrade phenol, the rule was α-MnO2>β-MnO2>γ-MnO2. Therefore, how to use the structure of MnO2, metal oxides and other factors to activate PMS to degrade dyes needs further study.
[0004] Chitosan (CS) is the only alkaline polysaccharide found in nature. It has the advantages of large specific surface area, rich active groups and stable crystal structure. Therefore, some studies have shown that the TiO2 / H2O2 system with CS added is more efficient than TiO2 / H2O2 in degrading methylene blue. The application of traditional photocatalysts is limited by their limited light responsiveness, insufficient adsorption capacity and easy aggregation. However, when CS is combined with semiconductor materials, it can effectively increase active sites, reduce band gap energy, enhance structural stability, and significantly promote the degradation of dyes in wastewater. Summary of the invention
[0005] The purpose of the present invention is to provide a chitosan-manganese oxide composite photocatalyst for activating PMS, a preparation process and an application thereof, so as to solve the technical problem that the existing oxidants have poor degradation effects and cannot meet application requirements.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A preparation process of a chitosan-manganese oxide composite photocatalyst for activating PMS, comprising the following steps:
[0008] (1) Weigh a certain amount of chitosan, add it to a mixture of ethanol and water, and ultrasonicate it to obtain a uniform dispersion system, which is recorded as solution A;
[0009] (2) Under continuous stirring, KOH is added to solution A. The solution obtained after KOH is fully dissolved is recorded as solution B;
[0010] (3) Dissolve KMnO4 in water and the resulting solution is referred to as solution C;
[0011] (4) Place solution C on a magnetic stirring device, add the solution B obtained above to solution C under stirring to obtain a brown-black liquid, continue stirring at room temperature, transfer to an oil bath pot or a hydrothermal reactor to react for a certain period of time, wait for the liquid to cool to room temperature after the reaction, pour out the supernatant liquid on the reactor, wash the solid at the bottom of the reactor alternately with water and ethanol several times, put the obtained solid in an oven to dry overnight, grind the dried solid to obtain a chitosan-manganese oxide composite photocatalyst for activating PMS.
[0012] Preferably, the mass of CS in step (1) is 50-200 mg.
[0013] Preferably, in step (1), the volume of ethanol is 15.3 mL, the volume of water is 18 mL, and the ultrasonic time is 5 min.
[0014] Preferably, the mass of KOH in step (2) is 6.1 g and the stirring time is 1 h.
[0015] Preferably, in step (3), 1.58 g of KMnO4 is dissolved in 25 mL of deionized water, and the resulting solution is recorded as C.
[0016] Preferably, in step (4), after stirring at room temperature for 4 hours, the mixture is transferred to an oil bath at 80°C and stirred for 24 hours. After the liquid is cooled to room temperature, it is washed alternately with deionized water and ethanol several times. The obtained solid is placed in a 60°C oven and dried overnight. The dried solid is ground to obtain a chitosan-manganese oxide composite photocatalyst for activating PMS.
[0017] Preferably, after continuing to stir at room temperature for 4 hours in step (4), the brown-black liquid is transferred to a 100 mL reactor and hydrothermally reacted at 160° C. for 12 hours. After the reactor is cooled to room temperature, it is washed alternately with water and ethanol several times, the collected solid is placed in a 60° C. oven and dried overnight, and the dried solid is ground to obtain a chitosan-manganese oxide composite photocatalyst for activating PMS.
[0018] The invention also provides an application of a chitosan-manganese oxide composite photocatalyst for activating PMS in dye degradation in water.
[0019] Preferably, the dye comprises one or more of MB and TB.
[0020] Compared with the prior art, the present invention has significant technical advantages, which are specifically reflected in the following aspects. These advantages not only deepen the understanding of the present invention on the relevant chemical reaction mechanism, but also bring revolutionary progress to practical applications:
[0021] (1) In terms of the innovative preparation of photocatalysts, the present invention cleverly utilizes the chemical reaction between CS (chitosan) and potassium permanganate to successfully synthesize chitosan-modified manganese oxide photocatalysts. This innovation not only enriches the types of photocatalysts, but also achieves efficient degradation of MB (methylene blue) and TB (toluidine blue) under mild conditions. The introduction of chitosan not only greatly optimizes the pore size distribution of manganese oxide, making the pore size of the two samples CS-AM and CS-CM increase by about 4-5 times compared with the unmodified AM, but this structural optimization directly improves the adsorption capacity and degradation efficiency of the catalyst for dyes, making the degradation rate of the two dyes jump to more than 92%. Through meticulous single-factor experimental analysis, the present invention further clarifies the optimal range of CS addition and PMS (peroxymonosulfate) concentration, which provides a scientific basis for parameter regulation in practical applications. Kinetic studies show that the degradation of MB follows the first-order kinetic model, while TB is more in line with the second-order kinetic model. This finding helps the present invention to more accurately predict and control the degradation process. In addition, the strong alkalinity of the photocatalyst itself further promotes the degradation efficiency of the dye by the photocatalyst, which is of immeasurable value for improving the flexibility and economy of the actual production process.
[0022] In the exploration of the degradation mechanism, the present invention found that PMS can generate SO4-· (sulfate radical) under the activation of light, and ·OH (hydroxyl radical) and SO4-· together constitute the dominant free radicals in the CS-AM / PMS system, which not only significantly accelerate the degradation process of the dye, but also effectively promote the redox cycle between Mn(Ⅲ) / Mn(Ⅳ). This discovery provides a new perspective for improving the activity of photocatalysts. Therefore, the strategy of using CS-AM photocatalyst to activate PMS in the present invention shows great application potential in the degradation of dyes in water, marking a solid step forward in the present invention in dealing with environmental pollution issues.
[0023] (2) The present invention has also made a breakthrough in the preparation process of nanomaterials. The chitosan-manganese oxide (CS-AM, CS-CM) nanomaterials prepared by the oil bath method or the hydrothermal method, through advanced characterization methods, the present invention clearly observed that the introduction of CS significantly improved the specific surface area and pore structure of the catalyst. This structural optimization directly led to a significant increase in the pore volume. Compared with pure manganese oxide (AM), its pores increased by about 4-5 times, which is crucial for improving the adsorption and catalytic performance of the catalyst.
[0024] In the advanced oxidation / photocatalytic synergistic degradation experiment, the present invention used PMS as an oxidant and CS-manganese oxide as a photocatalyst to systematically study the degradation of MB and TB dyes. The results showed that the addition of CS increased the adsorption sites on the surfaces of CS-AM and CS-CM, thereby promoting the effective capture and degradation of dye molecules. Under the optimal conditions (CS addition amount of 167 mg, PMS concentration of 10 mg / L, pH value of 11), the degradation rates of MB and TB by CS-AM were as high as 94.5% and 92.2% respectively in just 150 minutes, which far exceeded similar catalysts. In addition, CS-AM also showed excellent cyclic stability. Even after 5 cycles, its degradation rate of MB and TB remained above 82%, which fully demonstrated the durability and economy of the catalyst of the present invention.
[0025] Free radical quenching experiments further revealed that singlet oxygen ( 1 O2) plays a key role in the degradation of dyes. The decomposition of PMS under light and the sulfate radicals and hydroxyl radicals generated after activation by Mn(Ⅲ) jointly promote 1O2 is generated, and the superoxide anions generated by the manganese oxide in CS-AM under light excitation effectively supplement the consumption in the Mn(Ⅲ) / Mn(Ⅳ) cycle transformation, ensuring the continuous generation of singlet oxygen. This discovery not only deepens the understanding of the advanced oxidation / photocatalytic synergistic mechanism of the present invention, but also provides new ideas and approaches for the development of more efficient and environmentally friendly water treatment technologies.
[0026] In summary, the present invention has made significant progress in the preparation of photocatalysts, performance optimization, and exploration of degradation mechanisms, providing strong technical support for solving environmental pollution problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Schematic diagram of the synthesis of CS-AM and CS-CM;
[0028] Figure 2 SEM images of AM (a), CS-AM (b), and CS-CM (c);
[0029] Figure 3 EDS images of AM (a), CS-AM (b), and CS-CM (c);
[0030] Figure 4 Infrared spectra of CS, CS-AM, and CS-CM;
[0031] Figure 5 XRD spectra of CS, AM, CS-AM, and CS-CM;
[0032] Figure 6 XPS spectra AM (a), CS-AM (b), CS-CM (c), Mn2p, O 1p full spectra AM (a1), (a2), CS-AM (b1), (b2), CS-CM (c1), (c2);
[0033] Figure 7 BJH pore size distribution curves of CS-AM (a), CS-CM (b), and AM (c);
[0034] Figure 8 Comparison of the degradation performance of AM, CS-AM, and CS-CM on MB (a) and TB (b), the degradation curves of different CS addition amounts on MB (c) and TB (d) under the oil bath method at 80°C, and the degradation curves of different CS addition amounts on MB (e) and TB (f) under the hydrothermal method at 160°C;
[0035] Fig. 9Comparison of the degradation performance of PMS, PMS+CS-AM, and PMS+CS-CM on MB (a) and TB (b), as well as the degradation curves of different PMS concentrations on MB (c) and TB (d);
[0036] Fig.10 Degradation curves of MB (a) and TB (b) by CS-AM at different pH values;
[0037] Fig.11 Degradation curves of CS-AM to different initial concentrations of MB (a) and TB (b);
[0038] Fig.12 Figure 2 shows the catalytic kinetic model of MB (a) and the kinetic model of TB (b);
[0039] Fig.13 It is the degradation cycle diagram of MB and TB by CS-AM;
[0040] Fig.14 This is a diagram showing the effect of free radical quenching on the CS-AM / PMS system. DETAILED DESCRIPTION
[0041] The present invention is further described in detail below in conjunction with specific embodiments. It should be emphasized that the following description is only exemplary and is not intended to limit the scope and application of the present invention. 1. Experimental part
[0042] 1.1 Chemicals and Reagents
[0043] Chitosan, potassium permanganate, potassium hydroxide, sodium hydroxide, hydrochloric acid, ethanol, potassium persulfate, methylene blue, toluidine blue. All solutions were prepared with deionized water.
[0044] 1.2 Preparation of catalyst
[0045] Oil bath method MnO xPreparation of composite materials (CS-AM). First, a certain amount of CS (50 mg, 84 mg, 167 mg, 200 mg) was weighed, and the weighed CS was added to a mixture of 15.3 mL of ethanol and 18 mL of deionized water, and ultrasonicated for 5 minutes to obtain a uniform dispersion system, which was recorded as solution A. Under continuous stirring conditions, 6.1 g of KOH was added to solution A, and the solution obtained after stirring for 1 hour was recorded as solution B, and then 1.58 g of KMnO4 was dissolved in 25 mL of deionized water, and the obtained solution was recorded as solution C. Finally, solution C was placed on a magnetic stirring device, and at a certain stirring speed, the above-obtained solution B was added to solution C to obtain a brown-black liquid. After stirring at room temperature for 4 hours, it was transferred to an oil bath at 80°C and continued to stir for 24 hours. After the liquid was cooled to room temperature, it was washed alternately with deionized water and ethanol several times, and the obtained solid was placed in a 60°C oven and dried overnight. The dried brown solid was ground and stored for later use. In addition, pure amorphous MnO without adding CS was added. x , denoted as AM. This reaction mainly utilizes potassium permanganate and ethanol to undergo redox reaction to reduce manganese to manganese (III) and manganese (IV).
[0046] Hydrothermal MnO x Preparation of composite materials (CS-CM). In order to consider the influence of different crystal forms on the performance of the catalyst, in the process of preparing CS-CM, the amounts of CS, KMnO4, and KOH were kept unchanged, and the reaction conditions were changed from oil bath to hydrothermal. The solution B obtained above was added to solution C to obtain a brown-black liquid. After stirring at room temperature for 4 hours, the brown-black liquid was transferred to a 100mL reactor and reacted at 160°C for 12 hours. After the reactor was cooled to room temperature, it was washed alternately with deionized water and ethanol several times, and the collected solids were placed in a 60°C oven and dried overnight. Grind the dried brown solid and store it for later use. The schematic diagram of the synthesis steps is shown in the figure. Figure 1 .
[0047] The preparation technology principle of the present invention:
[0048] Preparation of MnO by oil bath method x The detailed process of the composite material (CS-AM) and its technical analysis are as follows. First, a certain amount of chitosan (CS) was accurately weighed, the specific amounts were 50 mg, 84 mg, 167 mg and 200 mg respectively. These different doses of CS were intended to explore their effects on the performance of the composite material. Subsequently, the accurately weighed CS was slowly added to a carefully proportioned mixture of 15.3 mL of ethanol and 18 mL of deionized water. The addition of ethanol helps the dissolution and dispersion of CS, while deionized water ensures the purity of the reaction system. After ultrasonic treatment for 5 minutes, CS formed a uniform dispersion system in the mixed solution, which is labeled as solution A in the present invention. This step ensures the full dispersion of CS and lays a solid foundation for subsequent reactions.
[0049] Under continuous stirring, 6.1 g of potassium hydroxide (KOH) was slowly added to solution A. KOH, as an alkaline catalyst, not only promoted the dissolution of CS, but also participated in the subsequent redox reaction and had an effect on the MnO x After stirring for 1 hour, the obtained solution was recorded as B. At this time, KOH had been fully mixed with CS and solvent to form a favorable x Growth microenvironment.
[0050] Next, 1.58 g of potassium permanganate (KMnO4) was dissolved in 25 mL of deionized water, and the resulting solution was recorded as C. KMnO4 is MnO x The main source of MnO, its concentration and solubility directly affect x The amount and structure of the solution C were measured. Solution C was placed on a magnetic stirring device, and the solution B obtained above was slowly added to solution C at a certain stirring speed. During this process, a complex redox reaction occurred between CS, KOH and KMnO4 to form a brown-black liquid mixture. Stirring was continued at room temperature for 4 hours to ensure that the reaction was fully carried out.
[0051] Subsequently, the mixture was transferred to an oil bath at 80°C and stirred for 24 hours. The oil bath method provides a stable heating environment, which is conducive to the formation and stabilization of the composite material structure. After 24 hours, the liquid was cooled to room temperature and washed alternately with deionized water and ethanol several times to remove unreacted raw materials and by-products. The obtained solid was placed in a 60°C oven and dried overnight to completely remove moisture and solvent. The dried brown solid was ground to obtain the composite photocatalyst CS-AM.
[0052] In the process of exploring the preparation process of composite photocatalysts, it is crucial to control the dosage of each raw material and optimize the process parameters. The dosage of CS affects the structure and properties of the composite material; the dosage of KOH is directly related to the reaction rate and MnO x The amount of KMnO4 generated determines the concentration of MnO x purity and structure. In addition, parameters such as oil bath temperature, stirring speed and reaction time also have a significant impact on the performance of the composite material. Through careful design and optimization, the present invention successfully prepared a composite photocatalyst CS-AM with excellent performance and achieved unexpected technical effects.
[0053] Next, the present invention turns to the hydrothermal method to prepare MnO xDetailed process of composite material (CS-CM). In order to further explore the influence of different crystal forms on catalyst performance, in the process of preparing CS-CM, the present invention keeps the dosage of CS, KMnO4 and KOH unchanged, but changes the reaction conditions from oil bath to hydrothermal. The solution B obtained above is added to solution C to obtain a brown-black liquid mixture. After stirring for 4 hours at room temperature, the brown-black liquid is transferred to a 100mL reactor and reacted at 160°C for 12 hours. The hydrothermal method provides a high temperature and high pressure environment, which is conducive to the formation of a specific crystal form of MnO x After the reaction, the reactor was cooled to room temperature and washed alternately with deionized water and ethanol for several times. The collected solid was placed in a 60°C oven and dried overnight. The dried brown solid was ground to obtain the composite photocatalyst CS-CM.
[0054] By comparing the composite photocatalysts prepared by the oil bath method and the hydrothermal method, the present invention found that different crystal forms of MnOx have a significant impact on the performance of the catalyst. This discovery not only enriches the present invention's understanding of the composite photocatalyst preparation process, but also provides valuable experience for the subsequent catalyst design and optimization.
[0055] 1.3 Photocatalytic degradation experiment
[0056] The degradation experiments were carried out under the irradiation of a 300W xenon lamp light source (PLS-SXE300+ / UV, Beijing Perfect Light Technology Co., Ltd., China). All photodegradation experiments were carried out in a 100mL beaker. PMS was added to the mixed solution of dye solution and catalyst and placed under a xenon lamp for irradiation and degradation. The degradation of the dye by catalysts with different CS contents was studied while changing several factors: different amounts of CS added, initial concentration of dye, concentration of PMS, pH, and the stirring speed was fixed at 600rpm. The addition of PMS and the adjustment of pH were completed before degradation. Before the start of degradation, the suspension was placed in the dark for 60min to achieve adsorption-desorption equilibrium.
[0057] During the illumination process, samples were taken at regular intervals, centrifuged (10000 rpm, 10 min), and filtered through a 0.22 μm polyethersulfone membrane filter. The optical absorbance of the dye at the maximum absorption wavelength was measured using an ultraviolet-visible spectrophotometer (UV-2600, Shanghai Shimadzu Global Laboratory Consumables Co., Ltd, China). The calculation formula for the photodegradation efficiency is (Eq. (1)):
[0058] Dye removal rate (%) = (1-C t / C0)×100 (1)
[0059] Where C0 is the initial concentration of the dye, C t is the corresponding concentration of the dye after different periods of illumination.
[0060] In the repetitive experiment, after each cycle experiment, the catalyst does not need to be washed. The catalyst that has been reacted is directly collected and placed in a 60°C oven for drying for the next cycle experiment. All experiments were repeated 5 times.
[0061] 1.4 Characterization and analytical methods
[0062] Scanning electron microscopy (SEM, SUPRA 55Sapphire, GRE) was used to observe the morphology and structure of the photocatalyst surface under the condition of platinum spray pretreatment. Fourier transform infrared spectrometer was used to study the surface functional groups of the photocatalyst. The XRD spectrum of the photocatalyst was analyzed by X-ray diffractometer (X-Pert PRO, MiniFlex600) at a voltage of 40KV, a current of 15mA, a scanning rate of 0.02° / s, and a scanning angle of 5-80°. The carbon, oxygen, and manganese elements present in the photocatalyst were analyzed by X-ray photoelectron spectroscopy. The absorbance of MB and TB at 664nm and 640.4nm was analyzed by ultraviolet spectrophotometer.
[0063] 2. Results and Discussion
[0064] 2.1 Material characterization
[0065] Scanning electron microscopy was used to characterize the MnO x The morphology of AM, CS-AM and CS-CM was analyzed. Figure 2 and Figure 3 As shown. Figure 2 AM( Figure 2 (a) The sample presents a flake structure. After adding CS, the morphology of the samples prepared by the two methods changes significantly, but due to the different temperatures, the morphologies of the two are also different. CS-AM ( Figure 2 (b)) samples present a stacked sheet-like, porous structure; CS-CM ( Figure 2 (c)) shows that the sample has both sheet and rod shapes. It can also be seen in the figure that the three samples exist at the nanoscale. The thickness of the nanosheet is about 2 to 5 nm.
[0066] exist Figure 3 In the EDS diagram, it was found that the distribution of C element in CS-AM and CS-CM samples was consistent with the distribution of O and Mn elements in AM sample, indicating that CS was successfully introduced into the composite material, so that it was uniformly modified on the surface of manganese oxide.
[0067] (1) FT-IR
[0068] FT-IR spectrum Figure 4 As shown, 1653cm -1 The corresponding peak is the amide group of CS, 1434 cm -1 is an alcohol group (CH-OH). However, when CS undergoes redox reaction with KMnO4, the above peak position will shift and -1 The characteristic peak of manganese oxide, Mn-O, appears. At the same time, it can be seen from the figure that CS-AM and CS-CM have -1 and 3000cm -1 The characteristic peaks on the left and right are stronger than the peak intensity of AM, and the peak intensity at different temperatures is also different.
[0069] (2)XRD
[0070] The structures of CS, AM, CS-AM and CS-CM were analyzed by XRD spectra. Figure 5 According to the XRD spectrum, the present invention can see that 12.9 0 , 25.1 0 MnO x The characteristic diffraction peaks of MnO2 and the broad reflection peak at 20.4° attributed to CS disappeared, and other new peaks appeared. The peak intensity of manganese oxide with CS added was higher than that of manganese oxide itself, indicating that the addition of CS improved the performance of MnO2. x At the same time, the characteristic peaks of CS-AM prepared by oil bath method are sharper and stronger than those of CS-CM prepared by hydrothermal method.
[0071] (3)XPS
[0072] The complete spectra of CS-AM and CS-CM and the spectral regions and corresponding contents of O and Mn were analyzed using XPS spectra. Figure 6 As shown. From the spectrum, it can be seen that the peak intensities of C1s and O1s of CS-AM and CS-CM are higher than those of AM, indicating that the content of the two elements has increased, indicating that CS has been successfully introduced. Figure 6 As can be seen from (a1, b1 and c1), the XPS spectrum of O1s can be divided into two peaks, corresponding to the Mn-O and Mn-OH bonds, respectively, indicating that the main components of the sample are manganese oxide and manganese hydroxide, and in the presence of CS, the content of Mn-O and Mn-OH changes. It can be seen from the figure that manganese oxide may be wrapped by a large number of hydroxyl groups, and in order to promote the electron exchange at the interface between manganese oxide and water, the hydroxide formed by the oxide is consumed. Figure 6As can be seen from (a2, b2 and c2), the manganese element in CS-AM and CS-CM is mainly Mn(Ⅳ). The contents of Mn(Ⅳ) in the two samples are 46.27% and 56.26%, respectively, and the contents of Mn(Ⅲ) are 37.5% and 29.94%, respectively. The presence of CS promotes the mutual conversion of Mn(Ⅲ) and Mn(Ⅳ).
[0073] (4) BET
[0074] As shown in Table 1, due to the addition of biopolymer CS, the average particle size of CS-AM and CS-CM samples is much larger than that of AM itself, and the pore size increases by about 4-5 times that of AM, indicating that the addition of CS will lead to the X The N2 adsorption-desorption isotherms and Barrett Joyner-Halenda (BJH) pore size distribution curves of the three samples were tested at 77K. The results are as follows: Figure 7 As shown in the figure, it was found that the N2 adsorption-desorption isotherms of the three samples can be classified as type IV adsorption isotherms. At the same time, according to the IUPAC classification, it was found that the three samples have typical mesoporous structures and hysteresis loops. However, with the addition of CS and the increase of temperature, the mesoporous structure in the samples is lost, causing the hysteresis loop to move toward a higher relative pressure.
[0075] Table 1
[0076]
[0077] 2.2 Catalytic performance
[0078] 2.2.1 Effect of CS addition on the two dyes
[0079] In order to study the role of CS in the sample, experiments were conducted to investigate the effect of CS addition on the dye. In these experiments, the present invention investigated the effect of too much or too little CS addition on the dye and the effect of temperature on the degradation of the dye. Figure 8 (a) Figure 8 In (b), by comparing the degradation curves of MB and TB, it is found that when CS participates in the preparation process of the two different preparation methods, the sample performance is improved. It can be seen that the introduction of CS helps to improve the catalytic activity of the samples prepared by the two different preparation methods. Figure 8It can be seen from (cf) that the amount of CS added must be within an appropriate range. The amounts of CS added are 0, 50 mg, 84 mg, 167 mg, and 200 mg, respectively. When the amount added is 167 mg, the degradation rates of MB and TB are 94.5% and 92.2%, respectively. It can be seen that the optimal amount added is 167 mg. Too high or too low is not conducive to degradation. This may be because CS will prevent electrons from returning, recombining with holes, and causing electrons to react with PMS. When the amount of CS added is too high, after the redox reaction between CS and potassium permanganate occurs, too much CS will occupy the catalytic active sites of the catalyst; and when the amount of CS added is too little, the adsorption sites of the catalyst will be insufficient. Both will lead to a decrease in the dye degradation rate. Figure 8 (e) Figure 8 It can also be observed in (f) that the adsorption performance of CS-CM prepared by the same raw materials under hydrothermal conditions at 160°C is inferior to that of CS-AM prepared by the oil bath method at 80°C. Therefore, the temperature should be controlled during the sample preparation process. The temperature range is within 60-100°C, and the best temperature is controlled at 80°C in the oil bath.
[0080] 2.2.2 Effect of PMS concentration on dye degradation
[0081] In the advanced oxidation process, the photocatalyst generates electron-hole pairs after light excitation, and then uses the active substances generated by the combination of oxidants and catalysts to degrade the dye. Therefore, the oxidant also plays a vital role in the degradation of the dye. Fig. 9 (a) Fig. 9 In (b), by comparing the degradation curves of MB and TB, it is verified that the addition of PMS promotes the degradation of dyes in the two samples. Fig. 9 (c) Fig. 9 (d) It can be seen that when the concentration of PMS increases to 10 mg / L, the degradation rates of the two dyes are both above 90%, but when the concentration of PMS increases from 10 mg / L to 20 mg / L, the degradation rates of the two dyes gradually decrease. Therefore, the addition of PMS concentration should be appropriate. The PMS concentration is in the range of 0-20 mg / L, and the optimal concentration is 10 mg / L. When the concentration is too low, it is impossible to generate enough 1 O2 promotes dye degradation, and this trend also reflects the synergistic effect of the samples prepared by the two methods and PMS. However, the reason for the decrease in dye degradation rate may be that the excessive oxidant quenches OH·.
[0082] 2.2.3 Effect of pH on dye degradation
[0083] In order to study the effect of pH on the degradation of dyes, the effects of different pH on the two dyes were investigated. Fig.10 (a) Fig.10As can be seen in (b), strong alkaline and acidic conditions are conducive to dye degradation. When the pH of the dye is a strong base, the degradation rates of both dyes are over 90%, and when the pH is acidic, the degradation rates of both dyes are over 85%, because MB and TB are cationic dyes and will be adsorbed on the negatively charged photocatalyst. In alkaline solutions, due to the increase in electrostatic attraction, the surface charge of the photocatalyst is negatively charged, and the electrostatic attraction promotes the adsorption of positively charged dyes. When at a lower pH, H + It will compete with cationic dyes, thereby reducing the adsorption of dyes on the photocatalyst surface. However, when the pH is neutral, due to the presence of amine and carboxyl groups on CS that strongly interact with protons, a small amount of sample is dissolved, resulting in a reduction in adsorption sites on the material surface. At the same time, the decrease in pH will also change the charge on the surface of manganese oxide from neutral to positive, resulting in a decrease in the adsorption of cationic dyes. Therefore, the degradation rate of dyes under neutral conditions is reduced. When the pH is in the range of 5-11, the sample itself is alkaline. At pH = 11, the degradation rates of MB and TB are the best, with degradation rates of 94.5% and 92.2%, respectively. A decrease in pH is not conducive to degradation.
[0084] 2.2.4 Effect of different initial concentrations on dye degradation
[0085] like Fig.11 (a) Fig.11 As shown in (b), with the increase of the initial concentration of MB and TB dyes, the degradation rate of the two dyes decreases. When the initial concentration of the dye is too high, due to the limited adsorption sites of the CS-AM sample itself, a large number of dye molecules will be free in the solution, resulting in a decrease in the degradation rate of the dye.
[0086] 2.2.5 Catalytic kinetic model
[0087] like Fig.11 (a) Fig.11 (b), the lower the initial concentration of the dye, the more conducive it is to degradation, which is also reflected in the kinetic models of MB and TB at different concentrations, e.g. Fig.12 The catalytic kinetics are consistent with equation (2) and equation (3).
[0088] from Fig.12 It can be seen that the initial concentration of the dye is too high, which is not conducive to the degradation of the dye. This is reflected in the kinetics. The lower the initial concentration of the dye, the higher the kinetic constant. At the same time, it can be seen that the kinetic model of MB conforms to the pseudo-first-order catalytic kinetics, and the kinetic model of TB conforms to the pseudo-second-order catalytic kinetics.
[0089] ln(C t / C0)=-k1t (2)
[0090] Where C0 is the initial concentration of the dye, Ct is the corresponding concentration of the dye after illumination for different time t, and k1 is the degradation rate constant.
[0091] (1 / C t -1 / C0)=k2t (3)
[0092] Where C0 is the initial concentration of the dye, C t is the corresponding concentration of the dye after illumination for different time t, and k2 is the degradation rate constant.
[0093] The fitting results showed that the linear regression of MB degradation by CS-AM was consistent with the first-order kinetics, while the catalytic degradation of TB was consistent with the second-order kinetics.
[0094] 2.3 Cyclic performance
[0095] Fig.13 It reflects the stability of CS-AM in the degradation of MB and TB dyes. It can be seen from the figure that in the first three cycle experiments, the degradation rate of MB remained at about 90%, and the degradation rate of TB remained at about 87%. After five cycles, the degradation rate of the two dyes dropped to about 82%, indicating the stability of CS-AM in the degradation of MB and TB dyes. The reason for the decrease in the degradation rate of MB and TB may be that part of the photocatalyst collection was lost during the cycle experiment, or the CS was partially dissolved. Comparing the experimental results of this experiment with other reports (Table 2), it is proved that CS-AM has great potential for the treatment of MB and TB dyes in wastewater, which is superior to the existing technology.
[0096] Table 2 Comparison of the degradation ability of dyes by CS-AM and photocatalysts reported in the literature
[0097]
[0098]
[0099] literature:
[0100] [1]Dawadi S, Gyawali K, Katuwal S, et al. Degradation of Methylene BlueUsing Hydrothermally Synthesized α-Manganese Oxide Nanostructures as aHeterogeneous FentonCatalyst[J]. Journal of Nanomaterials, 2022, 2022(1):3405066.
[0101] [2]LiY, Li M, Zhu C, et al. Main factors for photocatalytic degradation of rhodamine B byMoS2 activatedPMS[J]. Materials Letters, 2023, 341: 134191.
[0102] [3]Kiwaan HA, Atwee TM, Azab EA, et al. Photocatalytic degradation of organic dyes in the presence of nanostructured titanium dioxide [J]. Journal of Molecular Structure, 2020, 1200: 127115.
[0103] [4]Ramesh M.CuO as efficient photo catalyst for photocatalyticdecoloration of wastewater containing Azo dyes[J].Water Practice&Technology,2021,16(4):1078-1090.
[0104] 2.4 Degradation mechanism
[0105] The advanced oxidation process used in the present invention is to use peroxymonosulfate (PMS) or peroxydisulfate (PDS) as an oxidant to generate highly active sulfate free radicals (SO4 - · / SO5 - ·) to degrade the target pollutants. PMS has an asymmetric structure, so it is easier to be activated by light than PDS. In addition, hydroxyl radicals (OH·) can also be used to activate PMS. To verify the degradation of dyes by free radicals, 0.5 mL of quencher (MeOH, IPA, FFA, KI) was introduced to quench the free radicals in the mixed solution of the catalyst and then the experiment was carried out. Fig.14 It can be seen that O2 - , 1 O2、OH、SO4 - Together they act as ROS to participate in the degradation of dyes, among which 1O2 plays a major role. Therefore, the present invention believes that the generation of active oxygen not only promotes the degradation of dyes, but also promotes the redox of Mn(Ⅲ) / Mn(Ⅳ). At the same time, Shi et al.'s research shows that Mn(Ⅳ) (eg = 0) is more likely to combine and adsorb with PMS than Mn(Ⅱ) (eg = 2) and Mn(Ⅲ) (eg = 1), which not only improves the recycling efficiency of Mn(Ⅳ) / Mn(Ⅲ), but also further promotes the activation of PMS. The PMS of the present invention is excited to generate SO4 under light. - · and OH - , and then generate OH· and O2, O2 gains electrons to generate O2 - ·, then under the action of PMS, Mn(Ⅲ) is oxidized to Mn(Ⅳ), and Mn(Ⅳ) is - · is reduced to Mn(Ⅲ) and generates 1 O2 not only promotes the degradation of dyes, but also promotes the cyclic transformation of Mn(Ⅲ) / Mn(Ⅳ) (Eq.4 and 11). At the same time, SO4 generated during the degradation reaction - The main reason why · and OH· have little effect on dyes is that they are converted into 1 O2 and O2 - ·, while O2 - ·Then the reaction generates 1 O2. For 1 The specific reactions for the generation of O2 are as follows.
[0106]
[0107] SO4 - +OH - →SO4 2- +OH· (2)
[0108] HSO5→SO5 - +H + +e - (3)
[0109] Mn(Ⅲ)+HSO5-→Mn(Ⅳ)+SO4 - +OH - (4)
[0110] HSO5 - →SO5 2- +H + (5)
[0111] HSO5 - +SO5 2- →HSO4 - +SO4 2- + 1 O2 (6)
[0112] HSO4 - +OH→SO4 - +H2O (7)
[0113] 2SO5 - +H2O→2HSO4 - +1.5 1 O2 (8)
[0114] 2SO4 - +2OH - →2SO4 2- +2OH·+O2 (9)
[0115] O2+e - →O2 - · (10)
[0116] Mn(Ⅳ)+O2 - →Mn(Ⅲ)+O2 (11)
[0117] O2 - ·+OH·→ 1 O2+OH - (12)
[0118] In summary, the generation pathways of ROS in the CS-AM / PMS system mainly include: ① PMS decomposes into SO4 when exposed to light - ·, while SO4 - After a series of reactions, it is finally produced 1 O2 (Eq. (1)-(6)). ②PMS is activated by Mn (Ⅲ) to generate SO4 - · and OH· (Eq. 4 and 9). ③ The oxygen adsorbed on the surface of CS-AM obtains electrons to generate O2 - ·, and then reacts with OH· to generate 1 O2 (Eq. 10 and 12).
[0119] The degradation mechanism of dyes by CS-AM / PMS system is as follows: First, HSO5 in PMS - Decomposed into SO4 under light - ·, and then contact with CS-AM to form Mn(Ⅲ)-HSO5 - , in e - Under the acceptor, Mn(Ⅲ) is oxidized to Mn(Ⅳ), SO4 - After a series of reactions, O2 is generated, which serves as e - The donor promotes O2 - ·, which in turn promotes the reduction of Mn(Ⅳ) to Mn(Ⅲ) and the decomposition of PMS, and also promotes1 The generation of O2 and the valence cycle of Mn.
[0120] 3. Conclusion
[0121] The present invention successfully prepares CS-AM and CS-CM nano photocatalysts by oil bath method or hydrothermal method, and the synthesis process is simple. CS is used as both a reaction raw material and an important component of the catalyst, which can increase the pores of CS-AM and CS-CM, increase the adsorption sites on the catalyst surface, and is conducive to the adsorption of dyes on the catalyst surface, thereby improving the degradation rate of the dyes. CS-AM has a strong synergistic effect in the advanced oxidation / photocatalytic degradation of dyes by activating PMS, and its degradation rates for MB and TB reach 94.5% and 92.2% respectively. CS-AM also has good cyclic use stability, which can reduce the material cost in actual use.
[0122] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A preparation process of a chitosan-manganese oxide composite photocatalyst for activating PMS, characterized in that: The following steps are involved: (1) Weigh a certain amount of chitosan, add it to a mixture of ethanol and water, and ultrasonicate it to obtain a uniform dispersion system, which is recorded as solution A; (2) Under continuous stirring, KOH is added to solution A. The solution obtained after KOH is fully dissolved is recorded as solution B; (3) Dissolve KMnO4 in water and the resulting solution is referred to as solution C; (4) Place solution C on a magnetic stirring device, add the solution B obtained above to solution C under stirring to obtain a brown-black liquid, continue stirring at room temperature, transfer to an oil bath pot or a hydrothermal reactor to react for a certain period of time, wait for the liquid to cool to room temperature after the reaction, pour out the supernatant liquid on the reactor, wash the solid at the bottom of the reactor alternately with water and ethanol several times, put the obtained solid in an oven to dry overnight, grind the dried solid to obtain a chitosan-manganese oxide composite photocatalyst.
2. The preparation process of the chitosan-manganese oxide composite photocatalyst according to claim 1, characterized in that: The mass of CS in step (1) is 50-200 mg.
3. The preparation process of the chitosan-manganese oxide composite photocatalyst for activating PMS according to claim 1, characterized in that: The volume of ethanol in step (1) is 15.3 mL, the volume of water is 18 mL, and the ultrasonic time is 5 min.
4. The preparation process of the chitosan-manganese oxide composite photocatalyst according to claim 1, characterized in that: The mass of KOH in step (2) is 6.1 g and the stirring time is 1 h.
5. The preparation process of the chitosan-manganese oxide composite photocatalyst according to claim 1, characterized in that: In step (3), 1.58 g of KMnO4 was dissolved in 25 mL of deionized water, and the resulting solution was recorded as C.
6. The preparation process of the chitosan-manganese oxide composite photocatalyst according to claim 1, characterized in that: In step (4), after stirring at room temperature for 4 hours, the mixture is transferred to an oil bath at 80°C and stirred for 24 hours. After the liquid is cooled to room temperature, it is washed alternately with deionized water and ethanol several times. The obtained solid is placed in an oven at 60°C and dried overnight. The dried solid is ground to obtain a chitosan-manganese oxide composite photocatalyst.
7. The preparation process of the chitosan-manganese oxide composite photocatalyst according to claim 1, characterized in that: Step (4) After continuing to stir at room temperature for 4 hours, the brown-black liquid was transferred to a 100 mL reactor and hydrothermally reacted at 160° C. for 12 hours. After the reactor was cooled to room temperature, it was washed alternately with water and ethanol several times. The collected solid was placed in a 60° C. oven and dried overnight. The dried solid was ground to obtain a chitosan-manganese oxide composite photocatalyst.
8. A chitosan-manganese oxide composite photocatalyst prepared according to the process according to any one of claims 1 to 7.
9. Use of the chitosan-manganese oxide composite photocatalyst according to claim 8 for dye degradation in water.
10. The use of the chitosan-manganese oxide composite photocatalyst for degrading dyes in water according to claim 9, characterized in that: The dye includes one or more of MB and TB.
Citation Information
Patent Citations
Preparation method of crosslinked chitosan-manganese dioxide composite adsorbing material
CN103041787A
Chitosan-manganese dioxide composite adsorption material and preparation method thereof
CN110787774A